Radioembolization for the Treatment of Primary and Metastatic Liver Cancers - Lee, Eun Jeong (Nucl Med Mol Imaging, 2019)
Radioembolization using (90)Y microspheres (glass or resin) has been introduced as an effective intraarterial therapy for unresectable primary and metastatic liver cancers. Although the basic therapeutic effect of chemoembolization results from ischemia, the therapeutic efficacy of radioembolization comes from radiation. Furthermore, compared with surgical resection and local ablation therapy, radioembolization is available with less limitation on the sites or number of liver cancers. The radioisotope (90)Y is a β-radiation emitter without γ-radiation, with the emission of secondary bremsstrahlung photons and small numbers of positrons. Administration of (90)Y microspheres into the hepatic artery can deliver a high dose of radiation selectively to the target tumor with limited radiation exposure to the surrounding normal parenchyma, and has low systemic toxicity. In general, radioembolization has been considered for patients with unresectable primary or metastatic liver-only or liver-dominant cancers with no ascites or other clinical signs of liver failure, life expectancy of > 12 weeks, and good performance status. Here, we review the current radioactive compounds, pretreatment assessment, and indications for radioembolization in patients with hepatocellular carcinoma, intrahepatic cholangiocarcinoma, and liver metastases from colorectal cancer.